2012
DOI: 10.4236/jmp.2012.310185
|View full text |Cite
|
Sign up to set email alerts
|

Probe and Emission Spectrometry Diagnostics in Hollow Cathode Magnetron

Abstract: This paper deals with the characterization of an ionized physical vapor deposition (IPVD) by means of hollow cathode magnetron. Langmuir probe, optical emission spectroscopy measurements were used to study a mechanism for the production of excited argon and copper atoms and ions. The kinetic processes of excitation were considered and the main processes were determined using results of measurements. The pressure range is 0.5 - 10 mTorr with 1- 5 kW discharge power. Plasma parameters such as electron densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The work [31] considers mechanism for the production of excited atoms and ions of buffer gas and target in a high density plasma. It was shown that the ion emitted intensity J(ion) ∝ n 2 e , if main ionization occurs by an electron impact from the ion ground state and dominant loss is due to diffusion.…”
Section: Figures 3(amentioning
confidence: 99%
“…The work [31] considers mechanism for the production of excited atoms and ions of buffer gas and target in a high density plasma. It was shown that the ion emitted intensity J(ion) ∝ n 2 e , if main ionization occurs by an electron impact from the ion ground state and dominant loss is due to diffusion.…”
Section: Figures 3(amentioning
confidence: 99%